Correlating Student’s Vocabulary Mastery With Their Reading Comprehension Through Narrative Text - Ade Mulyadi; Lulu Lutfillah (Jurnal Fakultas Keguruan & Ilmu Pendidikan Kuningan, 2022)
This study aim to determine how the correlation between students' vocabulary mastery and students' reading comprehension skills in narrative texts. The population in this study were 9th grade students of MTsN 4 Kuningan with a sample of 30 students. The technique for obtaining data is to collect data from students' vocabulary tests and students' reading comprehension tests in narrative texts, then calculate and analyze the scores of the two tests and conclude based on the data results. The data obtained from this study used the Pearson Product Moment Correlation Coefficient. The results of the research on the correlation between students' vocabulary mastery and reading comprehension in narrative texts found that rxy = 0.817 and r-table was 0.361. By comparing the value of rxy and the value of r-table, it is known that rxy is greater than r-table. With the hypothesis: If ro is greater than rt then there is a positive correlation and Ha is accepted. If ro is smaller than rt then there is no positive correlation and Ha is rejected and Ho is accepted. From the results of the hypothesis found that rxy is greater than r-table, which means the alternative hypothesis is accepted. Based on the findings above, it can be concluded that there is a positive correlation between students' vocabulary mastery and students' reading comprehension in narrative texts in grade 9 MTsN 4 Kuningan in the 2021/2022 school year.